'Powerful knowledge', 'cultural literacy' and the study of literature in schools. (14th June 2021) - Eaglestone, Robert
Abstract: There is no doubting the influence of E.D. Hirsch and Michael Young on UK education policy and practice over the last ten years. Hirsch's notion of 'cultural literacy' and Young's idea of 'powerful knowledge' are the theoretical drivers of a national shift towards 'knowledge‐led' or 'knowledge‐rich' school curricula. Evidence of this shift is plain to see in the current iteration of the National Curriculum for England and in the mission statements of a growing number of schools and academy trusts across the country. According to Robert Eaglestone, however, there is a mistake under the floorboards of the new, knowledge‐rich curriculum. It is a mistake that damages and distorts teaching in a number of curriculum subjects, but Eaglestone ‐ a literary critic and theorist ‐ focuses on its disastrous impact on the teaching of literature. Both Hirsch and Young fall prey to scientism : they take knowledge in the natural sciences as a template for knowledge across the board. Eaglestone shows first how scientism is baked into the theories of 'cultural literacy' and 'powerful knowledge', then how the adoption of these theories in schools has disfigured and diminished the teaching of literature. Eaglestone's argument is arresting, timely and compelling. For those tasked with planning and teaching English curricula in schools, his penetrating analysis of where things have gone wrong and how to put them right will be revelatory and transformative. And for those concerned with curriculum theory and education policy more generally, it will reinvigorate and reorient the debate about what is helpful and what is not in the work of E.D. Hirsch and Michael Young.